An Economics of Wellbeing: What Would Economics Look Like if it were Focused on Human Wellbeing?. (January 2014) - Pouw, Nicky; McGregor, Allister
Summary: This paper makes a number of fundamental proposals to reconsider economics by putting human wellbeing at the centre. It emerges from a pluralist perspective in economics and the ontological, conceptual, axiomatic and methodological propositions that are made lead to the construction of what we call an inclusive economy matrix (IEM). In particular, the paper draws on heterodox economics to redefine the scope of economics, economic agency, rational behaviour and put emphasis on wellbeing rather than welfare. Furthermore, from the acknowledgement of human wellbeing as a three‐dimensional concept, the economic aggregation problem is reconsidered and the methodological implications discussed. The IEM is proposed as a comprehensive and robust analytical framework that gives space to bring social equity and sustainable development considerations forward as a priori concerns for economic development. As such, the IEM can serve as a point of departure for formulating new research questions, exploring new relationships between human wellbeing and economic development, and building economic models that bring us closer to people's realities on the ground.